Cienca, mercado y desigualdad - Sandra Tolosa (Centre de Recherches sur les Mondes Américains, 2014)
This paper considers the problem of sharing archaeological pieces of the NOA region, special goods, during the historical period between the late nineteenth and early twentieth centuries. At that time, the rise in the explorations of that particular region called "calchaquí " was directly determined by the processes of formation of the collections - national and international -, together with the consolidation of archeology as a discipline, causing deep impacts in the territory. While sharing these special goods assumed various forms during these processes, as the involvement of multiple actors and different practices, we will focus in two aspects. First, the sale of parts in a small scale, with the intervention of commercial exchange money and second, the movement of this objects as gifts or donations. We will relate both modalities with the specific forms of social relations and positions between the participants and how they impact in the value of the objects.